Basic elements of a process line for anaerobicaerobic treatment of pig complexes manufactures - Skliar, Radmila; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна (My University, 2020)
Lack of systems for treatment of manure effluents leads to environmental pollution and requires additional costs to pay for discharges. The use of only aerobic treatment does not provide the required cleaning quality and leads to high capital and operating costs. Anaerobic-aerobic technology for the treatment of slurry allows achieving the required level of treatment with a significant reduction in capital and operating costs.
Keywords: systems for treatment; pollution; aerobic treatment; anaerobic-aerobic technology for the treatment; operating costs; manure from pig farms